Availability of macronutrients in lyophilized human milk used to supply the nutritional needs of preterm newborns (Research, Society and Development, 2022)
Human Milk (HM) is the optimal source of nutrition for preterm newborns (PTNBs). Still, adapting the appropriate nutrient supply for these babies is a major challenge. Lyophilization is a common procedure employed to conserve HM that enables reconstitution of the milk in different volumes, therefore it provides better control of nutrient content, and consequently facilitates adapting its nutritional content to better fulfill the needs of PTNBs. Thus, this study assessed the proximate composition of HM, lyophilized HM, and hydrated lyophilized HM. For that matter, mature HM of 20 mothers was collected and sampled into 3 sample pools (HM, lyophilized HM, and hydrated lyophilized HM) for further analysis to define their proximate composition. Results demonstrated that lyophilization increased by 8-fold ash, protein, lipid, and carbohydrate content, and energy values compared to HM. Moreover, dilution of 1 g of lyophilized HM with 3.5 g of water was proven ideal for babies weighing up to 1.5 kg, as it provides macronutrient concentrations that approach the recommended nutritional needs. Furthermore, lyophilized HM displayed potential as a possible replacement of infant formulas since, regarding macronutrients, it can supply the nutritional needs of PTNBs.